EFEKTIVITAS METODE TOTAL PHYSICAL RESPONSE (TPR) TERHADAP KETERAMPILAN MENYIMAK SISWA KELAS III MIN 1 GOWA - Nurul Istiqamah; Mantasiah R; Fatkhul Ulum (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2026)
Listening comprehension among third-grade students at MIN 1 Gowa was evaluated by examining the integration of the Total Physical Response (TPR) method. A quantitative quasi-experimental framework using a nonequivalent control group design was established, involving a cohort of 36 students in the experimental class and 35 students in the control class. While the experimental group received TPR training, the control group followed standard conventional teaching. The assessment metrics consisted of a ten-item test comprising five true-false queries and five multiple-choice questions. Empirical records show that the experimental group mean score surged from 23.89 in the pre-test to 51.39 in the post-test, whereas the control group progressed from 23.43 to 36.29. Wilcoxon test calculations indicated significance values of less than 0.001 for the experimental cohort and 0.002 for the control group, verifying distinct performance shifts in both settings. This divergence is further corroborated by a Mann-Whitney test yielding a significance value of 0.002, falling below the 0.05 threshold. Consequently, TPR serves as a highly reliable approach to strengthen students' receptive language competencies, offering an active, engaging, and meaningful instructional alternative for language classrooms.